Efficacy of catheter-based renal denervation in the absence of antihypertensive medications (SPYRAL HTN-OFF MED Pivotal): a multicentre, randomised, sham-controlled trial. Issue 10234 (2nd May 2020) - Böhm, Michael; Kario, Kazuomi; Kandzari, David E; Mahfoud, Felix; Weber, Michael A; Schmieder, Roland E; Tsioufis, Konstantinos; Pocock, Stuart; Konstantinidis, Dimitris; Choi, James W; East, Cara; Lee, David P; et al.
Summary: Background: Catheter-based renal denervation has significantly reduced blood pressure in previous studies. Following a positive pilot trial, the SPYRAL HTN-OFF MED (SPYRAL Pivotal) trial was designed to assess the efficacy of renal denervation in the absence of antihypertensive medications. Methods: In this international, prospective, single-blinded, sham-controlled trial, done at 44 study sites in Australia, Austria, Canada, Germany, Greece, Ireland, Japan, the UK, and the USA, hypertensive patients with office systolic blood pressure of 150 mm Hg to less than 180 mm Hg were randomly assigned 1:1 to either a renal denervation or sham procedure. The primary efficacy endpoint was baseline-adjusted change in 24-h systolic blood pressure and the secondary efficacy endpoint was baseline-adjusted change in office systolic blood pressure from baseline to 3 months after the procedure. We used a Bayesian design with an informative prior, so the primary analysis combines evidence from the pilot and Pivotal trials. The primary efficacy and safety analyses were done in the intention-to-treat population. This trial is registered at ClinicalTrials.gov, NCT02439749 . Findings: From June 25, 2015, to Oct 15, 2019, 331 patients were randomly assigned to either renal denervation (n=166) or a sham procedure (n=165). The primary and secondary efficacy endpoints were met, with posterior probability of superiority more than 0·999 for both. The treatment difference between the two groups for 24-h systolic blood pressure was −3·9 mm Hg (Bayesian 95% credible interval −6·2 to −1·6) and for office systolic blood pressure the difference was −6·5 mm Hg (−9·6 to −3·5). No major device-related or procedural-related safety events occurred up to 3 months. Interpretation: SPYRAL Pivotal showed the superiority of catheter-based renal denervation compared with a sham procedure to safely lower blood pressure in the absence of antihypertensive medications. Funding: Medtronic.